PEDAGOGICAL PREPARATION OF CAMP COUNSELORS FOR WORKING IN MODERN SCHOOL - Petrash, Elena; Sidorova, Tatyana; Pradun, Inna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article discusses the problem of pedagogical training of camp counselors for working at school. The authors note that the profession of counselor in modern conditions takes on a completely different meaning: the introduction of the counselor position in the staff of the modern school is associated not only with the organization of children's vacation, recreation and rehabilitation, but also with the need to include counselors in the school educational activities during the school year.The article presents an empirical research of the counselors importance and their role in a modern school: a description of diagnostic tools is given, the survey results are analyzed by the authors. Also the authors diagnose the qualities and knowledge needed to the modern counselor, determine the counselor’s mission in a school, conduct a comparative analysis of the counselor’s activities at the school and the summer camp, summarizing the points of view of students and teachers (class teachers, representatives of the administration of educational institutions). The data obtained during the experiment formed the basis to create the educational program “Camp counselor at school”, focused on the pedagogical training of counselors for working at schools. The article is intended for public reading and for those who are interested in the problems of modernization of the general education system.